2012
DOI: 10.1017/s0007114512003911
|View full text |Cite
|
Sign up to set email alerts
|

Blueberry intervention improves vascular reactivity and lowers blood pressure in high-fat-, high-cholesterol-fed rats

Abstract: Growing evidence suggests that intake of flavonoid-containing foods may exert cardiovascular benefits in human subjects. We have investigated the effects of a 10-week blueberry (BB) supplementation on blood pressure (BP) and vascular reactivity in rats fed a highfat/high-cholesterol diet, known to induce endothelial dysfunction. Rats were randomly assigned to follow a control chow diet, a chow diet supplemented with 2 % (w/w) BB, a high-fat diet (10 % lard; 0·5 % cholesterol) or the high fat plus BB for 10 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 69 publications
3
39
0
Order By: Relevance
“…Enhanced acetylcholine (Ach)-induced vasorelaxation was observed in young SHRs fed an 8% WB diet for 7 weeks . Reduced Phe-induced vasoconstriction and enhanced Ach-induced vasorelaxation has also been reported with a 2% highbush blueberry diet for 10 weeks in Wistar rats fed a high fat and cholesterol diet to induce endothelial dysfunction (Rodriguez-Mateos et al 2013).…”
Section: Introductionmentioning
confidence: 72%
“…Enhanced acetylcholine (Ach)-induced vasorelaxation was observed in young SHRs fed an 8% WB diet for 7 weeks . Reduced Phe-induced vasoconstriction and enhanced Ach-induced vasorelaxation has also been reported with a 2% highbush blueberry diet for 10 weeks in Wistar rats fed a high fat and cholesterol diet to induce endothelial dysfunction (Rodriguez-Mateos et al 2013).…”
Section: Introductionmentioning
confidence: 72%
“…It has previously been reported in human studies that consumption of antioxidant-rich blueberries could lower blood pressure (Basu et al, 2010;Cassidy et al, 2011;Rodriguez-Mateos et al, 2013). Furthermore, as described in the animal study by Xu et al (2013) the fermentation of bilberries by L. plantarum DSM 15313 resulted in the production of new phenolic compounds (i.e.…”
Section: Introductionmentioning
confidence: 88%
“…The effects of supplementation with blueberry for 10 weeks on endothelial function and BP were studied in rats fed a high-fat diet. The study showed that blueberry supplementation lowered SBP by 14% and improved endothelial dysfunction and aorta relaxation in response to acetylcholine [70]. Furthermore, a study evaluated the potential protective effects of seven phenolic acids, identified as metabolites of blueberry, on murine macrophage cell line RAW 264.7.…”
Section: Experimental Studiesmentioning
confidence: 99%